2001
DOI: 10.1034/j.1399-3054.2001.1120318.x
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of flowering and stem extension of the intermediate‐day plant Echinacea purpurea

Abstract: Intermediate-day plants (IDP) flower most rapidly and completely under intermediate photoperiods (e.g., 12-14 h of light), but few species have been identified and their flowering responses are not well understood. We identified Echinacea purpurea Moench as an IDP and, based on our results, propose a novel mechanism for flowering of IDP. Two genotypes of E. purpurea ('Bravado' and 'Magnus') flowered most completely (>/=79%) and rapidly and at the youngest physiological age under intermediate photoperiods of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…The similar results were reported by Singh et al (2013). Runkle and Heins (2001) reported that far red (FR) -deficient environments effectively retard stem extension in many herbaceous plants, they can delay flower initiation in some long day plants.…”
Section: Resultssupporting
confidence: 77%
“…The similar results were reported by Singh et al (2013). Runkle and Heins (2001) reported that far red (FR) -deficient environments effectively retard stem extension in many herbaceous plants, they can delay flower initiation in some long day plants.…”
Section: Resultssupporting
confidence: 77%
“…Although no flowering occurred in continuous SD or LD in the present experiments (Table 2), a small proportion (10–15%) of cv. Bravado plants flowered in 10‐h and 24‐h photoperiods in the experiments by Runkle et al (2001). This difference was attributed by the authors to the fact that the plants were raised in 14–16 h daylengths, conditions which are inductive to flowering in this plant (Runkle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Bravado plants flowered in 10‐h and 24‐h photoperiods in the experiments by Runkle et al (2001). This difference was attributed by the authors to the fact that the plants were raised in 14–16 h daylengths, conditions which are inductive to flowering in this plant (Runkle et al 2001). Partial induction could therefore have taken place before the experimental treatments were started.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the sequence of inductive conditions is crucial, dual induction photoperiodic plants will not flower in either constant SD or constant LD conditions and, hence, they are distinct from daylength neutral species (Heide 2004). Such a dual daylength response is also not to be confused with intermediate daylength responses where LD and SD inputs may be satisfied simultaneously (Runkle et al 2001).…”
Section: The Regulation Of Flowering Involves Multiple Adaptations Tomentioning
confidence: 99%